Analyzing Factors Influencing Accounting Application Adoption Using the Unified Theory of Acceptance and Use of Technology (UTAUT) Model Among F&B MSMEs in West Java - Tambunan, Naomi Agatha Dwi Putri (Journal Integration of Management Studies, 2023)
Micro, small, and medium-sized businesses are crucial to Indonesia's long-term economic success. MSMEs accounted for 97 percent of employment in Indonesia in 2021, generated 60.42 percent of the country's total investment, and produced 61.07 percent of the country's GDP. Despite their significance to the national economy, many MSMEs continue to face difficulties. Capital constraints are one such factor. Limited financial management ability was noted as a cause for the low level of loans extended to MSMEs in Indonesia. Previous research found that accounting apps can improve MSMEs’ financial management capabilities and thus increase their access to finance. Despite the advantages of accounting software and the availability of various free accounting apps, a low adoption rate of accounting apps is found in the highly competitive culinary MSMEs in West Java. This study used the Unified Theory of Acceptance and Use of Technology (UTAUT) to investigate the variables that affect the intentions and actual use of accounting apps in culinary MSMEs. According to UTAUT, performance expectation, effort expectancy, social influence, and facilitating circumstances impact behavioral intention to adopt a system, whereas facilitating conditions and behavioral intention influence actual usage of the system. The quantitative approach was used in data collection, using questionnaires sent out to West Java’s MSMEs in the culinary sector. The PLS-SEM was then used to analyze the 131 survey responses. The results showed that MSMEs' performance expectation, effort expectancy, and facilitating conditions positively affected their behavioral intentions to utilize accounting apps. Behavioral intentions and facilitating conditions also affected users' actual app utilization. Therefore, it is suggested that developers of accounting apps and the government use these variables to increase the usage of the applications. Future research may include broader predictors to explain better the usage of accounting apps in light of the study's limitations.